Effects of Magnetoelastic Interactions in Conductive Plates and Shells - Baghdasaryan, Gevorg; Mikilyan, Marine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph investigates the stability and vibrations of conductive, perfectly conductive and superconductive thin bodies in electromagnetic fields. It introduces the main principles and obtains basic equations and relations describing interconnected mechanical and electromagnetic processes in deformable electroconductive bodies placed in an external inhomogeneous magnetic field and under the influence of various types of force interactions. Basic equations and relations are addressed in the nonlinear formulation. A special emphasis is put on the mechanical interaction of superconducting thin bodies plates with magnetic field.
Governing equations and relations of magnetoelasticity of conducting bodies -- Main equations and relations of magnetoelasticity of thin plates and shells -- Natural magnetoelastic vibrations of conducting plates -- Natural vibrations of conducting shells in a stationary magnetic field -- Control and generation of resonant vibrations of parametric type -- Control of forced vibrations -- Main equations and relations of magnetoelastic vibrations and stability of superconducting body -- Superconducting plates -- Superconducting cylindrical shells.
Keywords: Mechanics, Applied; Solids; Mechanics; Mathematics -- Data processing; Materials -- Analysis; Solid Mechanics; Classical Mechanics; Computational Mathematics and Numerical Analysis; Characterization and Analytical Technique